2023
DOI: 10.1002/adom.202300124
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Applications of Heterostructure Materials for Broadband Ultrafast Photonics

Abstract: Bo Fu received his Ph.D. degree from Tsinghua University in 2015. After two years of research at the University of Cambridge, he began his independent career as an associate research professor at Beihang University. He has authored and co-authored more than 60 peer-reviewed papers, such as in Advanced Optical Materials, Laser & Photonics Reviews, Advanced Functional Materials, and Small (ESI highly cited paper). His research interests include ultrafast photonics, laser optics, and nanophotonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 192 publications
0
3
0
Order By: Relevance
“…Ultrafast lasers have been developed as an influential technology providing desired power and energy in optical communication and ultraprecision machining. , In order to obtain ultrafast lasers, saturable absorbers (SAs) without extra modulator are presented to modulate pulses in the resonator. Artificial SAs such as nonlinear polarization rotation and nonlinear amplifying loop mirrors were first employed for the generation of ultrafast pulses. , Nowadays, semiconductor SA mirrors have been widely used as typical real SAs in lasers . Nevertheless, the exquisite structure and complicated preparation process limit their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast lasers have been developed as an influential technology providing desired power and energy in optical communication and ultraprecision machining. , In order to obtain ultrafast lasers, saturable absorbers (SAs) without extra modulator are presented to modulate pulses in the resonator. Artificial SAs such as nonlinear polarization rotation and nonlinear amplifying loop mirrors were first employed for the generation of ultrafast pulses. , Nowadays, semiconductor SA mirrors have been widely used as typical real SAs in lasers . Nevertheless, the exquisite structure and complicated preparation process limit their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other types of SAs still need to be studied, especially real SAs with saturable absorption properties. Typical real SAs include semiconductor saturable absorber mirror and nanomaterials, such as metal nanoparticles, carbon nanotubes, graphene, topological insulator, black phosphorus, and transition-metal carbides/nitrides/carbonitrides (MXene) [ 8 , 9 , 10 , 11 , 12 ]. The saturable absorption characteristics towards incident light of real SAs are from the materials themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The saturable absorption characteristics towards incident light of real SAs are from the materials themselves. Nanomaterials have the advantages of a broadband nonlinear absorption, ultrafast recovery time, and high environmental stability, which have been used as SAs in 2- m laser systems to generate Q-switched pulses [ 11 , 12 , 13 , 14 ]. For example, in 2016, Yu et al first demonstrated a Q-switched laser based on black phosphorus as the SA, where the 731 ns Q-switched pulse was obtained in 2 m [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broadband saturable absorbers, especially in the infrared band range, play an irreplaceable role in ultrashort pulse lasers, 1,2 and the exploration of saturable absorbers in the infrared band is an important research topic in laser technology and laser physics. 3–5 Considering their energy structure, 6 small bandgap materials are suitable candidates for the broadband operation of saturable absorbers because of their optical response in the infrared band.…”
Section: Introductionmentioning
confidence: 99%